Application of matrix converter to doubly-fed induction motor for slip energy recovery with improved power quality - Altun, Hueseyin; Suenter, Sedat (Ieee, 2007)
This paper reports control of a doubly-fed induction motor with a matrix converter using the slip energy recovery principle. The proposed drive system uses a matrix converter to extract the slip energy from the rotor into the mains instead of using the line commutated cycloconverter or back-to-back PWM converter as a static frequency changer. The system enables operations at both sub-synchronous and super-synchronous speed regions. The obtained simulation results for various operating conditions are presented illustrating the good control performance of the system.
Joint Conference on Electromotion/IEEE Aegean Conference on Electrical Machines and Power Electronics/ -- SEP 10-12, 2007 -- Bodrum, TURKEY